ANALISIS TERJEMAHAN CERITA ANAK DALAM BUKU BILINGUAL BERJUDUL “MASARASENANI DAN MATAHARI” DAN “MASARASENANI AND THE SUN” OLEH MURTI BUNANTA - Vidyasari, Farah (LANTERN (Journal on English Language, Culture and Literature), 2012)
Indonesian students have to learn the English language because the language is an international language. Translation is one of the many ways to learn a foreign  language as what Newmark said. Therefore, the writer wants to write translation as a topic of this research. The writer uses bilingual book entitled “Masarasenani and The Sun” by Murti Bunanta. The purpose of this research is to analyze method related with translation process in that book and to analyze form and meaning shifts that may happen in the translation process in that book. To reach the aim the writer uses descriptive and qualitative method. There are 59 sentences in that book and all of the sentences are used as the population of this research. The results of this research show that the most frequent method used by the author is free translation. Then, although there are some meaning shifts happen they do not really change the whole message of the text. In addition, the form shift which often occurs a shift from simple sentences to complex sentences. After analyzing the form and meaning shift, on the whole, the message in the translation text is equivalent to the original text.